Cobalt corroles with phosphonic acid pendants as catalysts for oxygen and hydrogen evolution from neutral aqueous solution. Issue 46 (4th May 2017) - Sun, Huiling; Han, Yongzhen; Lei, Haitao; Chen, Mingxing; Cao, Rui
Abstract : The acid/base pendants at the secondary coordination sphere of cobalt corroles play significant roles in OER and HER. Abstract : Cobalt corroles with different acid/base pendants, L Br –Co, L COOH –Co, L PO(OH)2 –Co, and L CH2 PO(OH)2 –Co (L = 5, 15-bis-(pentafluorophenyl)-10-(4-dibenzofuran)corrole), were synthesized and examined as catalysts for oxygen and hydrogen evolution from neutral aqueous solutions. Co corroles with phosphonic acid pendants showed improved activities in both processes, highlighting the importance of the secondary coordination sphere in catalyst design.